Acceleration Profile of Elite Gaelic Football With Special Reference to Position of Play. Issue 6 (June 2020) - Ryan, Martin; Malone, Shane; Donnellan, Andrew; Collins, Kieran
Abstract : Abstract: Ryan, M, Malone, S, Donnellan, A, and Collins, K. Acceleration profile of elite Gaelic football with special reference to position of play. J Strength Cond Res 34(6): 1750–1758, 2020—The current study aimed to characterize the positional match-play demands of elite Gaelic football players with special reference to acceleration using predetermined 5-minute periods (epochs). Thirty-five male Gaelic players (mean ± SD, age: 24 ± 6 years; height: 180 ± 7 cm; mass: 81 ± 7 kg) across 5 playing positions (full-back, half-back, midfield, half-forward, and full-forward) were monitored during the investigation. Player movement was recorded during 19 matches using 4-Hz global positioning system technology (VXSport, New Zealand) resulting in 154 player observations. Global positioning system was used to record total distance (m), (high-speed running; m; ≥17 km·h −1 ), (very high-speed running distance; m; ≥22 km·h −1 ), the number of accelerations ( n ), duration of accelerations (s), peak acceleration (m), and distance of accelerations (m). Acceleration profiles were position dependent with midfielders found to have a high accumulation of acceleration movements when compared with all other positions ( p ⩽ 0.05). Declines of −2 to −32% for acceleration distance (m) depending on positional line of play were observed during match-play. Less high-speed running and very high-speed running distance was performed by the full-back line (high-speed running; −39% and very high-speed running; −36%) and full-forward line (−35%; −29%) when compared with half-back, midfielders, and half-forwards ( p = 0.01, d = 1.35–1.77). Similar trends were reported for peak acceleration distance ( p = 0.01, d = 1.15–1.93). The current investigation provides a greater understanding of temporal differences in acceleration profiles of playing position. We show that half-back, midfield, and half-forwards have the highest acceleration movements; these data can assist coaches in appropriately preparing players for the required acceleration distances required during match-play.